An Error Analysis for the Finite Element Approximation to the Steady-State Poisson-Nernst-Planck Equations (Advances in Applied Mathematics and Mechanics, 2018)
Poisson-Nernst-Planck equations are a coupled system of nonlinear partial differential equations consisting of the Nernst-Planck equation and the electrostatic Poisson equation with delta distribution sources, which describe the electrodiffusion of ions in a solvated biomolecular system. In this paper, some error bounds for a piecewise finite element approximation to this problem are derived. Several numerical examples including biomolecular problems are shown to support our analysis.